Development of A Risk-Based Pre-Tender Assessment Tool for Oil and Gas Construction Projects Using Analytical Hierarchy Process - Sudirman; Rosmariani Arifuddin; M Asad Abdurrahman (Testing Center for Oil and Gas LEMIGAS, 2026)
The pre-tender stage is a critical decision point in oil and gas construction projects, particularly in capital-intensive, technically complex environments, where inappropriate project selection may increase financial, technical, operational, and regulatory risks. In practice, contractors often rely on subjective judgment in early project evaluation due to the limited availability of structured, quantitative decision-support tools. This study aims to develop a risk-based pre-tender assessment tool to support project selection decisions in oil and gas construction projects in Indonesia. The study integrates a literature review with a questionnaire-based survey involving 90 experienced construction practitioners occupying supervisory and managerial positions. Data were analyzed using descriptive statistics and the Analytical Hierarchy Process (AHP) to determine the relative priority weights of evaluation criteria and sub-criteria.The results indicate that all major criteria contribute significantly to pre-tender decision-making, with financial aspects obtaining the highest priority weight (22.9%), followed by commercial (20.1%), technical (19.4%), legal and social (19.3%), and marketing aspects (18.3%). At the sub-criteria level, expected profit margin, implementation risk, and project owner legality emerged as dominant evaluation factors. A case study application further demonstrates the practical applicability of the proposed framework, with the pipeline installation project achieving a higher feasibility score (7.48) than the oil storage terminal project (6.32). Sensitivity analysis also confirms that the ranking results remain stable under alternative weighting scenarios.The findings demonstrate that the proposed framework provides a structured, transparent, and risk-informed approach for evaluating project feasibility during the pre-tender stage. The study contributes by developing an integrated weighting-based decision-support framework specifically tailored to the characteristics and risk exposure of oil and gas construction projects, thereby supporting more objective and consistent contractor decision-making.